Transfer of β-1,3-glucanase gene into banana for tolerance to Fusarium wilt disease race 1 using Agrobacterium-mediated transformation system - Subramaniam, Sreeramanan; Mahmood, Maziah; Rathinam, Xavier (Global Science Books, 2008)
Agrobacterium-mediated transformation of single buds in vitro grown banana cv. ‘Rastali’ (AAB) was done using the binary vector pROKla-Eg, harboring the soybean endo β-1,3-glucanase gene (Eg). Plasmid pROKla-Eg contained a neomycin phosphotransferase gene (nptII) as the selectable marker to identify the transformants. Treatment A contained kanamycin (kan) at 100 mgl-1 and treatment B contained geneticin G-418 at 50 mgl-1 in both MS medium supplemented 5 mgl-1 of BAP together with 2.7 g of gelrite agar. Single buds derived from multiple bud clumps, were the target explants for transformation. An assay was performed to identify the minimum concentration required for two antibiotics (carbenicillin and cefotaxime) that was most effective against Agrobacterium strains, LBA 4404, and the effect on tissue regeneration capacity. Even though the transformation frequency based on kan selection medium (treatment A) was higher, no transformants could be confirmed based on PCR and Southern blot analyses, compared to the use of geneticin (G-418) selection medium (treatment B). These results suggested that the use of G-418 as a selection agent is preferable to kan due to the lower concentration required to allow for the small numbers of putative transgenic cells in a large population of non–transformed ones to undergo multiplication and also reduced the occurrence of chimeras. The transgenic banana plantlets were inoculated with 2 × 106 spores ml-1 conidial suspension of Fusarium oxysporum f. sp. cubense (race 1) to evaluate the degree of tolerance and to investigate the effectiveness of the bioassay system as a potential tool for early screening. An assay of protein extract from the transgenic plantlets showed a significant increase in EG enzyme activity over the untransformed plantlets. The present Agrobacterium-mediated transformation protocol reported here is suitable for the use of tiny meristem tissues to obtain fungal disease tolerant or resistant banana through genetic engineering.